Mathematics Practice Sem 1 - Ibrahim, Bohari; Norhunaini, Mohd Shaipullah; Nur Fazliana, Rahim; Siaw, Emmerline Shelda; Farah Liyana, Azizan; Chew, Khui Tat; Tan, George Geok Shim; Ahmad Alif, Kamal; Abang Mohammad Hudzaifah, Abang Shakawi (UNIMAS Publisher, 2019)
Mathematics Practice Semester 1 is specially written for foudation students level taking Mathematics at Centre for Pre-University, Universiti Malaysia Sarawak or local matriculation centres. The objective of this book is to provide a comprehensive discourse of the basic concepts and foundation in Mathematics. This book contains ten chapters. Each chapter starts with a page of notes and formulae for easy reference. In each chapter, the concepts are explained clearly with real practice questions. Question and answer for each chapter provide a wide range of examination type question based on the concepts and theories learnt. Answers are also provided for all questions on each chapter. To optimize the effectiveness of this books, students are advised not to simply read the notes and formulae but instead to work out the solution and method on the space provided below the questions. All mathematical concepts are presented clearly in simple English for easy understanding. Practical questions have been incorporated to the chapters to enhance better understanding of the concepts. The book is also suitable for first year undergraduate Mathematics course for a degree or diploma programme.